Association between a frailty index derived from laboratory tests and clinical outcomes in critical care patients with asthma: a retrospective study based on the MIMIC-IV database - Qu, Jianmin; Wang, Tingting; Li, Zhe; Yu, Yi (Frontiers in Medicine, 2025)
BackgroundIn this study, we aimed to explore the association between elevated Frailty Index laboratory-derived (FI-Lab) levels and the prognosis in critically ill patients with asthma to advance clinical management strategies and optimize patient outcomes.MethodsA retrospective analysis was performed on intensive care unit (ICU) patients diagnosed with asthma identified from the Medical Information Mart for Intensive Care (MIMIC-IV, version 3.0) database. Demographic characteristics, clinical parameters, and FI-Lab values were collected for analysis. The prognostic factors were evaluated using multivariate Cox regression models.ResultsOur findings revealed a strong association between elevated FI-Lab levels and adverse clinical outcomes in ICU patients with asthma. Among the 2,339 patients, those presenting with higher FI-Lab scores at admission exhibited a significantly increased risk of complications, including prolonged ICU stays and higher mortality rates. Specifically, a 0.1-unit increase in the FI-Lab score was associated with a 1.32-fold increased risk of 28-day mortality [hazard ratio (HR) = 1.32, 95% confidence interval (CI): 1.17–1.50, p < 0.001], 1.25-fold increased risk of ICU mortality (HR = 1.25, 95% CI: 1.05–1.47, p = 0.011), and 1.33-fold increased risk of 90-day mortality (HR = 1.33, 95% CI: 1.20–1.48, p < 0.001). Additionally, when the FI-Lab scores were analyzed as categorical variables, significant associations with the 28-day, ICU, and 90-day mortality rates remained consistent across all models.ConclusionsElevated FI-Lab levels are a strong prognostic factor in ICU patients with asthma. Incorporating the FI-Lab into clinical evaluations may provide a new scientific basis for assessing the prognosis of severe asthma and potentially improving patient outcomes. Randomized controlled trials are required to validate our findings.